2021
DOI: 10.2174/1871520620666200908104835
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistance in Ovarian Cancer: Prospects for New Drugs

Abstract: : This review focuses on conventional treatment overview, signaling pathways and various reasons for drug resistance with understanding novel methods that can lead to effective therapies. Ovarian cancer is amongst the most common gynecological and lethal cancers in women from the age of 20-60. The survival rate is limited to 5 years due to diagnosis in subsequent stages with reoccurrence of tumor and resistance of chemotherapeutic. The recent clinical trails use combinatorial treatment of carboplatin and pacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…The anticancer effects of phytochemicals in ATC cells, including cell growth inhibition, suppression of angiogenesis, and autophagy modulation, promotion of apoptosis cell cycle arrest, and ROS activation are presented in Table I. Phytochemicals are generally considered to have the ability to reduce ROS activity in other cancers (87)(88)(89). It is unusual for phytochemicals to have the capacity to increase the activation of ROS in ATC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer effects of phytochemicals in ATC cells, including cell growth inhibition, suppression of angiogenesis, and autophagy modulation, promotion of apoptosis cell cycle arrest, and ROS activation are presented in Table I. Phytochemicals are generally considered to have the ability to reduce ROS activity in other cancers (87)(88)(89). It is unusual for phytochemicals to have the capacity to increase the activation of ROS in ATC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PTEN siRNA could eliminate the distinct proliferation capacity or metastasis ability between miR-4461 overexpression OC cells and control cells. Acquired cisplatin resistance is a serious problem for the therapy of OC patients (8,24). miRNAs actually participated in the regulation of tumorigenesis and drug resistance in OC (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols and flavonoids, such as resveratrol, genistein, curcumin, and quercetin, maintain the balance of antioxidant systems by scavenging ROS ( 100 103 ). Furthermore, preclinical studies showed that these antioxidant phytochemicals inhibit human cancers, including ovarian cancer, by anticancer activities, including anti-angiogenic, anti-proliferative, anti-inflammatory, and pro-apoptotic properties ( 100 103 ). The positive effects of antioxidant therapy have been reported in in vitro and in vivo animal studies.…”
Section: Targeted Therapy For Ovarian Cancer Based On Redox Modificationsmentioning
confidence: 99%
“…Polyphenols and flavonoids, such as resveratrol, genistein, curcumin, and quercetin, maintain the balance of antioxidant systems by scavenging ROS (100)(101)(102)(103). Furthermore, preclinical studies showed that these antioxidant phytochemicals inhibit human cancers, including ovarian cancer, by anticancer activities, including anti-angiogenic, anti-proliferative, anti-inflammatory, and pro-apoptotic properties (100)(101)(102)(103). The positive effects of antioxidant therapy have been reported in in vitro and in vivo animal studies.…”
Section: Suppressing Tumor Progression By Inhibiting Ros Generationmentioning
confidence: 99%